COMPARATIVE POLITICAL JOURNALISM IN SOUTH AMERICA: professional configurations and disputes over truth in Argentina, Brazil, and Uruguay - Schuliaquer, Ivan; Moreira Cesar, Camila (Brazilian journalism research, 2024)
ABSTRACT – This article analyzes the (re)configurations of political journalism in the face of the challenges of the contemporary information-communication ecosystem, political polarization, and disputes over the truth. It employs interviews, observations, and literature review to develop an unique model for comparative analysis of political journalism, applied to Argentina, Brazil, and Uruguay. The results indicate that, despite remaining continuities in the Latin American region, the characteristics of political journalism vary significantly between countries, impacting public debate. In Uruguay and Brazil, efforts are made to contain misinformation, while in Argentina, it is sometimes perpetuated by the journalists themselves. RESUMO – Este artigo analisa as (re)configurações do jornalismo político diante dos desafios do ecossistema infocomunicacional contemporâneo, da polarização política e das disputas pela verdade. Utiliza-se entrevistas, observações e revisão de literatura na elaboração de um modelo próprio para analisar o jornalismo político comparativamente, aplicado à Argentina, Brasil e Uruguai. Os resultados mostram que, apesar das continuidades existentes na América Latina, as características do jornalismo político variam significativamente entre os países, afetando o debate público. No Uruguai e no Brasil, busca-se conter a desinformação, enquanto na Argentina ela é, por vezes, alimentada pelos próprios jornalistas. RESUMEN – Este artículo analiza las (re)configuraciones del periodismo político ante los desafíos del ecosistema infocomunicacional contemporáneo, la polarización política y las disputas por la verdad. Se utilizan entrevistas, observaciones y revisión de literatura para desarrollar un modelo propio para analizar el periodismo político comparado aplicado a Argentina, Brasil y Uruguay. Los resultados indican que, a pesar de las continuidades existentes en América Latina, la configuración del periodismo político varía significativamente entre los países, afectando el debate público. En Uruguay y Brasil, se busca contener la desinformación, mientras que en Argentina esta es, a veces, alimentada por los propios periodistas.